Multi-user diversity gain in uplink cognitive radio systems with spectrum sensing reliability - Kim, Junsu; Shin, Yoan; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2010)
In this paper, we investigate the performance of opportunistic scheduling in uplink cognitive radio (CR) systems taking into account the spectrum sensing reliability of each CR user. In uplink CR systems, each secondary transmitter (CR user) has a spectrum sensing responsibility to protect the primary system, and the secondary receiver (base station) schedules the transmission opportunity for each CR user. Unlike non-CR multi-user systems, the spectrum sensing reliability may degrade the achievable multi-user diversity (MUD) gain. We propose novel scheduling schemes taking into account the spectrum sensing reliability and data channel quality simultaneously to improve the MUD gain in uplink CR systems. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03